Leadership Characters in Malaysian Religious-NGOs: An Introductory Overview - Mohd Faridh Hafez Mhd Omar; Sharifah Hayaati Syed Ismail; Ishomuddin Sulaiman Ilyas (Akademi Pengajian Islam Universiti Malaya, 2024)
Indexed by MyCite